(untitled) (Journal of Population and Development, 2025)
This article encompasses a comparative outlook of professional writing and creative writing. The purpose of the paper is to explore multiple dimensions of writing especially of scientific and creative writing. The professional writing incorporates resume, official letters, business letters, annual reports, grant proposal, memorandum, medical report, audit report, infrastructural design documents etc. Creative writing entails the writings such as stories, fairy tales, novels, epics, dramas, film scripts, reality show scripts, news etc. Both of the writing types are mostly sought after across the world. The importance of creative writing lies in creativity and nobility. Audiences seek to engage them with new things rather than old and outdated reading materials. They can experience newness in creative writing. However, in professional zones, the demand of professional writing for career search and progression is crucial and the learners have to invest much time in excelling professional writing for better and more effective communication. The formalities and norms of writing are rigidly observed in professional writing rather than in creative writing. The finding of the research is that creative writers need to have passion and curiosity to generate new things for a wide readership, whereas the professional writers must practice and develop skill for professional communication in written versions. This paper has been inscribed by using the secondary sources of information. The method used so far is qualitative.